ANALISIS WACANA LIRIK LAGU DAERAH KUTAI “BUAH BOLOK” DAN “NASI BAKEPOR” - Nur Bety (LOA: Jurnal Ketatabahasaan dan Kesusastraan, 2019)
Song is a means of conveying one's expression. This paper will describe the grammatical aspects and lexical aspects in the lyrics of the song "Buah Bolok" and "Nasi Bakepor". Descriptive qualitative method is  used in this paper. Discourse analysis in this song covers both grammatical and lexical aspects. Grammatical aspects of referring, recovering, percolating, and sequencing. The classical aspects of repetition, synonymy, collocation, hyponimi, and antonymia.